THE EFFECT OF BLENDED LEARNING ON EFL STUDENTS’ ACHIEVEMENT - Shofi, Syifa Najihah; Martina, Feny; Afriani , Zelvia Liska (Yayasan Darussalam Bengkulu, 2022)
The objective of this study was intended to find out the significant effect of blended learning with enriched virtual model on EFL students’ achievement. This study used a time-series design method. The sample in this research was 29 students in class IX C taken by performed a test to the population to determine their achievement in learning English. The researcher has given achievement tests to students and identified class who need treatment used blended learning with enriched virtual model to increase English learning achievement. The researcher was given the treatment used enriched virtual model in class. Pre-test were given before giving treatment. The result showed as follows: First, the pre-test score showed the average score is 61.72. After being given treatment, a post-test is given. The post-test result show the average value is 77.41 in this case the increase is 15.69. Second, the score of the independent t-test shows the significant value (2-tailed) is 0,000 < 0,05. In other words, H0 was rejected and Ha was accepted. It can be concluded that blended learning with enriched virtual model has a significant effect on the third grade of MTsN 2 Mukomuko in the academic year 2021/2022.